PEDAGOGICAL CONDITIONS IN PROVIDING THE QUALITY OF SYSTEM MANAGEMENT TRAINING OF FUTURE TACTICAL LEVEL OFFICERS - Buryy, S.; Bura, Yu. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2020)
The article reveals and substantiates the pedagogical conditions that determine the providing quality professional training of future officers, namely: didactic, academic pedagogical conditions in the educational process of higher military educational institution. Pedagogical conditions in the educational process of military management training form the basis in the formation of high military professionalism, which has the following components: system of professional knowledge and skills in the management of the unit, education and training of subordinate personnel; system of behavior qualities; system of moral and psychological qualities. The management culture of the officer and its practical importance for the officer in fulfilling the socially important professional duties are theoretically substantiated in the article. Organizational and methodological pedagogical conditions of the formation of management culture of future officers are measures of the educational process that ensure the subjective behavior of cadets, create favorable conditions for them as a full-fledged subject of the educational process. Methodological and organizational conditions of the educational process of higher military educational institution are the use of professionally oriented methods and didactic technologies of educational activities, which have a methodological reason to stimulate the development and improvement of thinking processes taking into account the age peculiarities, military-professional and management experience, future career prospects and job competencies of future officers; ensuring the development of the bases of management culture of cadets in educational activity. The organizational and pedagogical conditions of the formation of management culture of future officers include the creation of a professionally oriented learning environment in higher military educational institution; providing cross-curricular links between the disciplines that create favorable organizational conditions for the purposeful development of the educational process of military educational institution in the training of tactical level officers. Pedagogical conditions are the basis for mastering professional general theoretical disciplines by a future officer of the tactical level in education and the basis of management training as a military commander.